2008
DOI: 10.1051/dst:2007048
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein aggregation in heat-induced heat stability during milk powder manufacture

Abstract: -Although the inherent heat stability and the processes leading to the heat-induced coagulation of milk and reconstituted milk powders have been studied extensively, the processes that lead to heat-induced heat stability are less well established. An investigation has been undertaken into the effects of standardization with milk permeate or lactose and the heat-stabilization of milk powders. Standardized and unstandardized milk powders were produced in spring and autumn to determine seasonal effects on their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Using this technique, further resolution of the distribution of the particles in milk was obtained, allowing separation of 6 differently sized populations within the sample. These are indicated in Figure 1 as follows: peak 1 = large casein micelles with diameters >200 nm; peak 2 = small casein micelles with diameters in the range 160 to 80 nm; peak 3 = small protein aggregates and very small micelles with diameters 80 to 37 nm; peak 4 = whey proteins; peak 5 = small peptides; and peak 6 = small aromatic molecules (Williams et al, 2008).…”
Section: Casein Micelle Size From Individual Milk Samplesmentioning
confidence: 99%
“…Using this technique, further resolution of the distribution of the particles in milk was obtained, allowing separation of 6 differently sized populations within the sample. These are indicated in Figure 1 as follows: peak 1 = large casein micelles with diameters >200 nm; peak 2 = small casein micelles with diameters in the range 160 to 80 nm; peak 3 = small protein aggregates and very small micelles with diameters 80 to 37 nm; peak 4 = whey proteins; peak 5 = small peptides; and peak 6 = small aromatic molecules (Williams et al, 2008).…”
Section: Casein Micelle Size From Individual Milk Samplesmentioning
confidence: 99%
“…These heat treatments cause a number of competitive and often interdependent reactions in milk proteins, and many reactions also involve the non-protein constituents of milk. The heat-induced changes in milk have been the subject of many reviews and books [9,13,[21][22][23][24]27].…”
Section: Protein Interactions During the Manufacture Of Smpmentioning
confidence: 99%
“…Williams et al . () suggested that different aggregation processes are involved at different time–temperature combinations resulting to the creation of discretely differently sized populations of aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al . () very nicely described the effect of different heat treatments on the degree of dissociation and size of the formed soluble aggregates. The authors suggested that upon heating milk containing a mixture of casein micelles and whey proteins at 85 °C for 1800 s, a considerable dissociation of the whey protein/casein complexes from the micellar surface takes place, resulting in large soluble aggregates and hence only a slight increase of the micelle size.…”
Section: Introductionmentioning
confidence: 89%